Metal complexes of a novel heterocyclic benzimidazole ligand formed by rearrangement-cyclization of the corresponding Schiff base. Electrosynthesis, structural characterization and antimicrobial activity. Issue 12 (28th February 2018) - Casanova, I.; Durán, M. L.; Viqueira, J.; Sousa-Pedrares, A.; Zani, F.; Real, J. A.; García-Vázquez, J. A.
Abstract : One-pot electrochemical synthesis of metal complexes containing a novel heterocyclic benzimidazole ligand is reported and characterized. Abstract : The electrochemical oxidation of anodic metals (M = cobalt, nickel, copper, zinc and cadmium) in a solution of the ligand 1 H -anthra[1, 2- d ]imidazol-6, 11-dione-2-[2-hydroxyphenyl] [H2 L] afforded homoleptic [ML] compounds. The addition to the electrochemical cell of coligands (L′) such as 2, 2′-bipyridine (bpy) or 1, 10-phenanthroline (phen) allowed the synthesis, in one step, of heteroleptic [MLL′] compounds. The crystal structures of H2 L (1 ), [CoL(MeOH)]2 (2 ), [CoL(phen)]2 (3 ), [NiL(bpy)]2 (4 ), [CuL(bpy)] (5 ), [CuL(phen)] (6 ) and [CdL(bpy)]2 (7 ) have been determined by X-ray diffraction techniques. The crystal structures of2, 3, 4 and7 consist of dimeric species in which both metallic atoms are connected through two phenolate bridges in a penta-coordinated (2 ) or hexa-coordinated (3, 4 and7 ) environment. Copper compounds5 and6 are monomeric species with the metal in a pentacoordinated [N4 O] environment. In all the compounds, the main interactions responsible for the crystal packing are classic (N–H⋯O, O–H⋯N and O–H⋯O) and non-classic (C–H⋯O and C–H⋯N) hydrogen bond interactions, and π interactions (π–π-stacking and C–H⋯π). All compounds were also characterized by microanalysis, IR spectroscopy, FAB mass spectrometry and 1 H NMR spectroscopy. Magnetic susceptibility data were measured for2–4 over the temperature range 2–300 K, and their analysis has revealed the occurrence of intramolecular antiferromagnetic coupling for2 ( J = −2 cm −1 ) and ferromagnetic coupling for3 ( J = 7.8 cm −1 ) and4 ( J = 2.8 cm −1 ) [J being the isotropic magnetic coupling parameter]. The nature of the magnetic coupling in2–4 is correlated with the magnitude of the M–Ophenolate –M angle between the phenolate bridge and the metallic centers [M(ii ) = Co, Ni]. The in vitro antimicrobial properties of the novel ligand and its metal complexes were detected against Gram positive and Gram negative bacteria and fungi. [NiL(bpy)]2 and all tested Cd(ii ) complexes were the most active compounds, showing the highest inhibitory effect against bacilli (MIC 1.5–3 μg mL −1 ) and Sarcina, Streptococci and Haemophilus influenzae bacterial strains (MIC 12–50 μg mL −1 ), while almost no antifungal properties were observed.